Pendekatan Inquiri untuk Meningkatkan Aktivitas dan Prestasi Belajar Pendidikan Kewarganegaraan Siswa Kelas VI SDN 2 Natar Lampung Selatan - Nildawati, Nildawati (STKIP PGRI Bandar Lampung, 2022)
The purpose of this study was to determine the increase in activity and learning outcomes using the Inquiry Approach in class VI SDN 2 Natar in the 2019/2020 academic year. The research method uses Classroom Action Research which consists of 3 cycles, in each cycle there are 3 meetings consisting of 4 stages, namely planning, implementation, observation and reflection. The results showed that the application of the Inquiry approach could improve Civics learning outcomes in Reading Environmental Maps in Class VI students of SDN 2 Natar in the 2019/2020 academic year.